A continuum of bright and dark-pulse states in a photonic-crystal resonator - Su-Peng Yu; Erwan Lucas; Jizhao Zang; Scott B. Papp (Nature Communications, 2022)
A Kerr-nonlinear resonator with normal dispersion supports bright and dark pulse states. With photonic crystal ring resonators, this work demonstrates a continuum across these nonlinear states and explores the underlying mechanism.